STUDI GAMBARAN HASIL PEMERIKSAAN APUSAN DARAH TEPI PADA IBU HAMIL DI LABORATORIUM RSUD H.A.SULTHAN DAENG RADJA KABUPATEN BULUKUMBA - Rahmat Aryandi; Subakhir Salnus (Jurnal Kesehatan Panrita Husada, 2018)
During pregnancy, there will be a marked change in anatomy, physiology and biochemistry since the onset of pregnancy and often lack of nutrient intake. Hematologic disorder is often found in pregnant women because it causes pregnant women more susceptible to disturbances in blood circulation, The purpose of this study to determine the description of blood smear results in pregnant women in the laboratory RSUD H.A.Sulthan Daeng Radja District. This research is descriptive with laboratory observation approach. The sample used in this study were 30 samples of pregnant women who checked themselves in the Laboratory of RSUD H.A.Sulthan Daeng Radka Bulukumba District. The result of this research showed the result of peripheral blood smear on the morphology of erythrocytes using 30 samples of pregnant women showed 14 samples (46,66%) normocytic normochrom and the remaining 16 samples were morphological variation (53,33%), on morphological examination and platelet count with using 30 samples of pregnant women showed each 29 samples had morphology and normal platelet counts with respectively 96.66% percentage and platelet aggregation and decreased platelet count (thrombocytopenia) with each persentase 3.33%. At leukocyte morphology examination using 30 samples of pregnant women showed 29 samples had normal morphology with 96,66% percentage and one sample with hypersegmentation with percentage 3,33%. normal leukocyte count at 9 samples with percentage 30% and leukocyte count increased at 21 samples with percentage 70%.